Temperature Dynamics, Volatility, and the UK Demand for Natural Gas - Alec, Horton (2010)
The purpose of this paper is to consider how changes in temperature affect the volatility of the financial markets and overall demand for natural gas as released by the National Grid. Parts 1 to 3 of this paper provide an overview of the gas markets and the literature. Parts 4 and 5 provides the reader with an in depth analysis into temperature, demand and the financial markets. Part 4 finds a strong relationship between temperature and the demand for natural gas and clear evidence of seasonality in natural gas demand. Part 5 focuses on volatility and the financial markets. There is significant evidence that market volatility is greater during the winter months in comparison to the summer months. The market is also found to be largely inefficient, which is confirmed when testing the Efficient Market Hypothesis in part 5.1.